PENGARUH SOLVABILITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PT. ALAM SUTERA REALTY PERIODE 2010-2021 - Rusnaeni, Nani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
The development of the property industry in Indonesia, particularly represented by PT. Alam Sutera Realty, Tbk., has experienced fluctuations in line with economic dynamics. Solvency and profitability emerge as key factors influencing the company's value. This research aims to analyze how solvency and profitability contribute to the value of PT. Alam Sutera Realty, Tbk. during the period 2010-2021. The study employs a quantitative approach with secondary data analysis. Financial data for the company is obtained from PT. Alam Sutera Realty, Tbk.'s annual financial reports. Regression analysis is utilized to assess the relationship between solvency, profitability, and the company's value. The population in this study comprises the financial reports of PT. Alam Sutera Realty, Tbk. from 2010 to 2021. The results indicate that solvency and profitability significantly impact the value of PT. Alam Sutera Realty, Tbk. High solvency enhances the company's value, while a favorable level of profitability also contributes positively to an increase in the company's value.